STUDI BENTUK, FUNGSI DAN MAKNA ORNAMEN MAKAM DI KOMPLEKS MAKAM RAJA-RAJA BUGIS - Meisar Ashari (Pascasarjana Institut Seni Indonesia Surakarta, 2013)
This article is the result of a study about a physical cultural legacy that is also an artistic product left over from the heydayof the Islamic dynasty from the 17th to the 19th century. For this reason, there are two artistic aspects that need to be observedclosely in the analysis of the form, function, and meaning of grave ornaments, namely the aesthetical context or the presentationof the ornaments, including the form and expertise which gave rise to the style, and secondly the context of meaning,including the message and connection of the symbols on the ornaments, or the symbolic value. The investigation of theaesthetical value of the form and function of grave ornaments aims to discover the meaning that has become associated witha particular work, and as such, the existence of the ornaments is analyzed based on an interactional and interpretationalanalysis through an archeological aesthetical approach. The interactional analysis is carried out in order to gain an intersubjectiveinterpretation of the data that is obtained by using ethical research or based either on the data in a bibliographicalstudy or on the knowledge and opinion of the researcher. The goal of the analysis is to discover the form, function, andmeaning of the ornaments on the graves in the cemetery of Bugis kings. The benefit of the analysis is that it shows that theexistence of grave ornaments is not only a form of cultural identity of the local community but also provides a wealth ofinformation that is communicated through the visual symbols found in the patterns or motifs contained in the grave ornaments.Keywords: Form, function, meaning, and grave ornaments.